The benefits of mechatronically-guided railway vehicles: A multi-body physics simulation study. (May 2018) - Farhat, Nabilah; Ward, Christopher P.; Goodall, Roger M.; Dixon, Roger
Abstract: Mechatronically-guided railway vehicles are of paramount importance in addressing the increasing interest in reducing wheel-rail wear and improving guidance and steering. Conventional passively-guided rail vehicles are limited by the mechanical constraints of the suspension elements. Currently, a typical rail vehicle suspension needs to be sufficiently stiff to stabilize the wheelsets while being complaint enough to negotiate curved track profiles. The suspension is therefore a compromise for the contradictory requirements of curving and stability. In mechatronic vehicles, actuators are used with the conventional suspension components to provide additional stiffness or damping forces needed to optimise a vehicle for a wide variety of scenarios, and not rely on a sub optimal combination of passive components. This research demonstrates the benefits of active guidance and steering when compared to a conventional vehicle using simulation results from a multi-body simulation software Simpack. It also provides insights into the relative performance of the mechatronic schemes. The Simpack modeling allows for a complex model with high fidelity, which provides an additional level of proof of the control algorithms working on a real rail vehicle. Each vehicle is assessed in terms of guidance on straight track, steering on curved track, actuation requirements and wheel-rail wear. Significant benefits are demonstrated in one of the guided vehicles with independently-rotating wheelsets.